Strategi Place Triangle Pembangunan Pariwisata Berkelanjutan Berbasis Masyarakat Di Kota Kupang Nusa Tenggara Timur - Maria Bernadetha Ringa (Jurnal Inovasi Kebijakan, 2020)
The presence of tourism is proven to have had a positive impact on improving the welfare of the people in Kupang City, NTT, because it has created jobs for people around tourism destinations, such as: the growth of culinary businesses, shops, trade businesses, travel agencies, art shops and other tourism businesses. The role of government, private sector, and social capital is needed to support the success of community-based sustainable tourism in Kupang City. This study aims to find: (1) the right concept in the triangle for sustainable tourism development; (2) strategies for the role of the government, private sector, and community participation in sustainable tourism development in Kupang City; (3) to design the right strategy in the development of sustainable tourism in Kupang City. This research was conducted in Kupang City, East Nusa Tenggara Province, in six sub-districts, where there are tourist destinations, both natural tourism, marine tourism, religious tourism, and artificial tourism. The samples in this study were 270 respondents. Data were collected, to strengthen the tourism strategy in Kupang City using a SWOT analysis. The results of the research and data analysis show that: (1) the roles of the government, private sector and society are implemented in the triangle concept, (2) the right strategy in community-based tourism development in Kupang City, namely: Weaknesses and Opportunities, which is a strategy to minimize weaknesses by taking advantage of opportunities.